Frequency of Preterm Birth among Patients with Preeclampsia at a Tertiary Care Hospital - Seema; Aftab, Nabeela; Kashish; Batool, Kaneez; Nizamani, Hajra; Mehnaz; Fatima, Aryan (Indus Journal of Bioscience Research, 2025)
Background: Preterm birth is a leading cause of neonatal morbidity and mortality worldwide, with particularly high rates in South Asia. Preeclampsia significantly increases the risk of medically indicated preterm delivery, yet local data remain limited. Objective: To determine the frequency of preterm birth among women with preeclampsia at a tertiary care hospital in Pakistan and explore associated maternal and neonatal factors. Methodology: A descriptive cross-sectional study was conducted in the Department of Obstetrics & Gynaecology, PUMHS, Nawabshah, over six months, from September 2024 to March 2025. A total of 147 women aged 18–40 years, admitted with preeclampsia, were consecutively recruited after informed consent. Women with multiple gestations, chronic hypertension, gestational diabetes, or severe coexisting illnesses were excluded. Data on demographics, obstetric history, clinical parameters, and pregnancy outcomes were collected. Analysis was performed using SPSS 26, applying descriptive statistics, Chi-square, t-tests, and Mann–Whitney U tests, with p ≤0.05 as significant. Results: Preterm birth occurred in 51% of women with preeclampsia. Severe preeclampsia, earlier gestational age at diagnosis, heavier proteinuria, higher blood pressure, and obesity were significantly associated with preterm delivery. Preterm infants had markedly lower birth weights (1981 g vs. 3329 g) and were more often delivered by cesarean section (84% vs. 33%). Conclusion: Preeclampsia is strongly linked with high rates of preterm birth and adverse neonatal outcomes. Findings highlight the need for improved risk stratification, preventive interventions, and strengthening of antenatal care policies in resource-limited settings.